Cost-Effectiveness Analysis of Budesonide/Formoterol and Fluticasone/Salmeterol for Stable Chronic Obstructive Lung Disease - Amelia Lorensia; Monica Dyah Puspitasari; Soedarsono Soedarsono; Rivan Virlando Suryadinata (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Chronic Obstructive Pulmonary Disease (COPD) is one of the four largest types of non-communicable diseases in the world, requiring long-term and routine treatment. Treatment with the inhalation route is in the form of a dry-powder inhaler (DPI) which is easy to use and carry. Combination of corticosteroid and long-acting beta-2 agonist (LABA) in the form of DPI available in Indonesia are budesonide/formoterol and salmeterol/fluticasone. The purpose was to identify therapy was more cost-effective between budesonide/formoterol than fluticasone/salmeterol in clinical symptoms using COPD assessment test (CAT) value and lung function in FEV1/FVC (Forced Expiratory Volume in First Seconds/Forced Vital Capacity) ratio.Methods: This research study was pre-post design with cost-effectiveness analysis, in outpatient COPD patients in a hospital in Gresik Regency, from October 2019 to January 2020. There were two outcomes of respondents in this study, namely lung function seen from the value of FEV1, and clinical symptoms seen from the value of CAT. The study used hospital perspective.Results: There were 38 respondents involved. Fluticasone/salmeterol therapy was more effective than the budesonide/formoterol group in improving FEV1/FVC ratio, while budesonide/formoterol was more effective than the fluticasone/salmeterol group in improving clinical symptoms by CAT assessment. The average cost effectiveness ratio (ACER) value of lung function between the fluticasone/salmeterol group (IDR.176.465/Liter) was lower than that of budesonide/formoterol (IDR.296.832/Liter). The ACER clinical symptoms value between the fluticasone/salmeterol group (IDR.16,283/score) was smaller than that of budesonide/formoterol (IDR.17,340/score). Conclusion: Fluticasone/salmeterol was more cost-effective than budesonide/formoterol in improving lung function. Meanwhile, for clinical symptoms, fluticasone/salmeterol was trade-off with budesonide/formoterol.